2015
DOI: 10.1002/jts.22018
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Trauma and Combat During Deployment: Associations With Suicidal Ideation Among OEF/OIF/OND Veterans

Abstract: Compelling evidence has emerged on the association between military sexual trauma and suicide attempt; however, research investigating how sexual trauma during deployment relates to suicidal ideation has received considerably less attention and has yielded mixed findings. Furthermore, such research has not accounted for other types of trauma that may occur during deployment. Our objectives were to examine whether sexual trauma during deployment was associated with recent suicidal ideation, adjusting for exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The rise in suicides relative to the prevalence of sexual harassment and assault has led to several research studies in recent years. Among veterans of Operation Enduring Freedom (OEF) and Operation Iraqi Freedom (OIF), Monteith, Menefee, Forster, Wanner, and Bahraini () observed deployment‐related sexual trauma was associated with suicide ideation, after controlling for differences in age, gender, and combat exposure. Belik, Stein, Asmundson, and Sareen () examined sexual trauma among Canadian military personnel, and observed sexual trauma (e.g., rape, sexual assault) was associated with suicide attempts in both men and women, even considering sociodemographic and mental health disorders.…”
Section: Sexual Harassment and Suicide Riskmentioning
confidence: 99%
“…The rise in suicides relative to the prevalence of sexual harassment and assault has led to several research studies in recent years. Among veterans of Operation Enduring Freedom (OEF) and Operation Iraqi Freedom (OIF), Monteith, Menefee, Forster, Wanner, and Bahraini () observed deployment‐related sexual trauma was associated with suicide ideation, after controlling for differences in age, gender, and combat exposure. Belik, Stein, Asmundson, and Sareen () examined sexual trauma among Canadian military personnel, and observed sexual trauma (e.g., rape, sexual assault) was associated with suicide attempts in both men and women, even considering sociodemographic and mental health disorders.…”
Section: Sexual Harassment and Suicide Riskmentioning
confidence: 99%
“…Other studies have also found that the association between MST and adverse psychiatric outcomes remains significant when controlling for other types of interpersonal violence (e.g., childhood abuse, civilian sexual trauma) and combat (Kang, Dalager, Mahan, & Ishii, ; Luterek, Bittinger, & Simpson, ; Monteith et al., ). MST is also associated with more severe physical health outcomes and lower quality of life than civilian sexual trauma (Surís, Lind, Kashner, & Borman, ).…”
mentioning
confidence: 94%
“…Veterans who screen positive for MST are more likely to have a history of suicide attempt, relative to Veterans without MST (Kimerling, Gima, Street, Smith, & Frayne, ; Klingensmith, Tsai, Mota, Southwick, & Pietrzak, ; Pavao et al., ). Further, multiple studies suggest that MST is also associated with suicidal ideation (Gradus, Street, Suvak, & Resick, ; Klingensmith et al., ; Monteith, Menefee, Forster, Wanner, & Bahraini, ).…”
mentioning
confidence: 99%
“…This data-driven method allows for the simultaneous examination of predictors from a variety of domains and for the discovery of unanticipated associations with SI. The literature to date has largely documented hypothesis-driven, null-hypothesis-tested associations between gender, trauma, psychiatric symptomatology, and SI among veterans, which highlighted sexual harassment, PTSD, depression, and alcohol abuse as key predictors (Bryan et al, 2015;Gradus, Street, et al, 2013;Gradus et al, 2015;Jakupcak et al, 2009;Lemaire & Graham, 2010;Monteith et al, 2015;Pietrzak et al, 2010). This study extends that work by demonstrating that a supervised machine learning Variables with a dot to the right of the line contributed to predictive accuracy in the random forest, with higher numbers on the x-axis indicating stronger associations with suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented associations between sexual harassment during deployment and SI while accounting for mental health symptoms among female veterans specifically (Gradus, Street, et al., ). Recently, sexual harassment during deployment was shown to be associated with SI in a combined sample of male and female veterans after adjusting for combat exposure (Monteith, Menefee, Forster, Wanner, & Bahraini, ). Among military personnel and veterans currently enrolled in college classes, moderately sized associations were found for premilitary and military sexual trauma and SI in a gender‐stratified sample, although some were nonsignificant, likely owing to the small sample size (Bryan, Bryan, & Clemans, ).…”
mentioning
confidence: 99%